The Role of ChatGPT in Enhancing Argumentative Writing Skills of EFL Students through Formative Feedback - Setiawan, Virgin; Pariyanto (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
This research aims to analyze the role of ChatGPT’s formative feedback in improving the quality of EFL Students’ argumentative essay writing. The methodology involved a quantitative design with pre-feedback and post-feedback argumentative essays written by 31 participants. These essays were assessed by the argumentative writing rubric from SERP Institute which focusing in four aspects; argumentation, evidence, organization, and language. Scores were rated by two raters, with high interrater reliability confirmed by ICC value of .950. The result of this research revealed statistically improvement in the rating of argumentative essays after receiving formative feedback from ChatGPT, with the evidence aspect showing the highest mean increase (5.8387 points). This is based on the .Sig value of paired sample test of .000, it shows a significant improvement. Additionally, based on the interview responses, it is revealed that after utilizing the feedback from ChatGPT, the participants’ overall showed positive perceptions of ChatGPT, highlighting its usefulness in identifying weaknesses, improving structure, and generating ideas, although students noted that clear prompts were necessary. Keywords: Argumentative Writing, ChatGPT, EFL Learners, Formative Feedback, Interrater Reliability